Time-adjusted average Mayo endoscopic score predicts the risk of disease extent progression in distal ulcerative colitis patients. (18th May 2022) - Wan, Jian; Wang, Xuan; Zhang, Yujie; Xue, Xianmin; Jia, Hui; Wang, Min; Liang, Jie; Wu, Kaichun
Abstract: Background: Ulcerative colitis (UC) is a chronic lifelong disease. The disease extent of UC can progress over time. This study aimed to assess whether cumulative inflammatory burden (CIB) is associated with disease extension in distal UC (proctitis [E1] and left-sided colitis [E2]) patients, and to develop a quantified indicator of CIB. Methods: In this retrospective study based on a prospective registry, distal UC patients receiving colonoscopies in Xijing Hospital (Xi'an, China) from January 2000 to May 2019 were studied. We developed a new score, namely the time-adjusted average Mayo endoscopic score (TA-MES), calculated as dividing the sum of the cumulative average MES over a period of surveillance time by the length of the endoscopic examination interval, to quantify the CIB. Cox regression was used to identify other potential risk factors. Results: A total of 295 UC patients were followed for 1, 487.02 patient-years. Among them, 140 patients (47.5%) experienced disease extension. Multivariate analysis showed that the TA-MES was significantly associated with disease extension in E1 (hazard ratio [HR], 2.90; 95% confidence interval [CI], 1.58–5.33, P = 0.001) and E2 (HR, 1.89; 95% CI, 1.16–3.09, P = 0.011) patients. Other risk factors included hemoglobin of <90 g/L and appendiceal skip inflammation; the protective factors included age, E2 at diagnosis, former smoking, and 5-aminosalicylic acid dose. Otherwise, MES at diagnosis, maximal MES, and mean MES failed to estimate the risk of disease extension. Conclusion: TA-MES is a good quantified indicator of CIB and is independently associated with increased disease extension in distal UC patients. Whether the dynamic multiple scoring system could be used as a risk factor in other chronic relapsing–remitting diseases is a direction for future research.